Cervical Lymphangiomas in Children: Non-Surgical Treatment with Focus on Sclerotherapy. Literature Review (Global Journal of Medical Research, 2022)
Objectives To discuss the non-surgical strategies for the management of cervical lymphangiomas in children with particular attention to sclerotherapy Methods A literature review of the last fifteen years about sclerotherapy of cervical lymphangiomas in children was performed and the main sclerosing agents were reported highlighting the nature the mechanism of action and the rates of success recurrences and complications related to each and every substance furthermore the several steps of the procedure are illustrated Alternative approaches are also mentioned Results 47 articles were collected mostly dealing with sclerotherapy with OK-432 bleomycin pingyangmycin and doxycycline other potential substances include above all sodium tetradecyl-sulphate and ethanol Laser therapy and radio-frequency ablation are valid options in case of mucosal micro-cystic lesions oral medications e g Sirolimus and the newest target-therapies are added to local treatments in some Series
Keywords: cervical lymphangiomas; surgery; sclerotherapy; sclerosing agents